The CLASSROOM OBSERVATION IN ESP: A CASE STUDY OF MECHANICAL ENGINEERING STUDENTS’ EFL COURSE - Apriana Diana (Universitas Muhammadiyah Kotabumi, 2023)
This research work shed light on classroom observation to measure the implementation of ESP in Mechanical Engineering Course. Two lecturers of this major were observed by the writer during their English instructional classes. There was observation, syllabus document and semi-structured interview used as the instruments by the writer in gathering the data. These data were descriptively analyzed and reported to answer to the issues revealed as the background of the study. The classroom observation indicated that: 1) Both lecturers did not fully implement in their English classes; 2) All the elements of ESP, namely: needs analysis, syllabus design, teaching materials, learning activities, and evaluation needed to be developed and improved by these two lecturers; 3) There were several possible causes that made ESP implementation of these two lecturers became ineffective; a) the policy of the institution which managed English course of all non-English majors in integrated including syllabus design and text-book used, b) this policy made the lecturers difficult to modify their teaching activities and evaluation since the text-book used was not appropriate with students’ needs in this major, c) limited English prior knowledge of the students which made the lecturers hard to come to specific English without firstly equip the students with general English.